Analysis of Flood Vulnerability Level at Secondary Schools in Ranah Pesisir Sub-District - Wijayanto, Bayu; Cynthia, Fiona; Astuti, Juli; Femilia, Vanessa Nara; Rahman, Bima; Handayani, Alifvia Putri; Addawiyah, Jamiatul; Nofrion, Nofrion; Malusu, Daudi Richard; Gharamah, Fadhl Mohammed Awadh (Sustainability (STPP) Theory, Practice and Policy, 2025)
Ranah Pesisir Subdistrict, located in Pesisir Selatan Regency, is a flood-prone area due to its lowland geographical condition and proximity to the coastline and rivers. This study aims to analyze the flood vulnerability levels of secondary schools using a quantitative descriptive approach based on Geographic Information System (GIS). The study also seeks to describe the preparedness level of schools in mitigating flood disasters in Ranah Pesisir Subdistrict. Parameters analyzed include elevation, slope, rainfall, soil type, land use, and river proximity.The results show that the majority of secondary schools analyzed are located in zones categorized as "Vulnerable" to "Highly Vulnerable" to flooding. Schools such as UPT SMP Negeri 3 Ranah Pesisir, MTSN 2 Pesisir Selatan, MAN 2 Pesisir Selatan, and MTS Bahrul 'Ulum Sungai Tunu fall into the "Highly Vulnerable" category due to their low elevation, close proximity to rivers, and inadequate drainage systems. The dominant contributing factors are low elevation, proximity to rivers, and poor drainage infrastructure. Mitigation recommendations include the construction of protective embankments, improvement of drainage systems, disaster preparedness education, and the development of School Flood Contingency Plans. These findings are expected to serve as a basis for policymaking in disaster risk reduction efforts within the education sector, particularly in strengthening school infrastructure standards in flood-prone areas, establishing mandatory school-based disaster contingency plans, enhancing coordination between schools and local disaster management agencies, integrating flood preparedness into the school curriculum, and prioritizing infrastructure investments such as drainage rehabilitation and protective embankment construction for high-risk schools